4-substituted tert-butyl phenylazocarboxylates-synthetic equivalents for the para-phenyl radical cation - Höfling, Sarah; Bartuschat, Amelie; Heinrich, Markus (Angewandte Chemie International Edition, 2010)
First electrophile, then radical: 4-Substituted tert-butyl phenylazocarboxylates 1 are versatile synthetic equivalents of the para-phenyl radical cation 2. The tert-butyloxycarbonylazo group enables nucleophilic substitutions to proceed under mild conditions and can later be employed for the generation of aryl radicals. Copyright © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: arenes; aromatic substitution; nucleophilic substitution; radical reactions; synthetic methods

Fast and efficient 18F-labeling by [18F]fluorophenylazocarboxylic esters - Fehler, Stefanie; Maschauer, Simone; Höfling, Sarah; Bartuschat, Amelie; Tschammer, Nuska; Hübner, Harald; Gmeiner, Peter; Prante, Olaf; Heinrich, Markus (Chemistry - A European Journal, 2014)
Introduction of [(18) F]fluoride ion into the aromatic core of phenylazocarboxylic esters was achieved in only 30 seconds, with radiochemical yields of up to 95 % (85(±10) %). For labeling purposes, the resulting (18) F-substituted azoester can be further converted in radical-arylation reactions to give biaryls, or in substitutions at its carbonyl unit to produce azocarboxamides. Copyright © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
UnivIS-Import:2015-04-14:Pub.2014.nat.dchph.lphch.fastan

Fluoro-substituted phenylazocarboxamides: Dopaminergic behavior and N-arylating properties for irreversible binding - Bartuschat, Amelie; Schellhorn, Tamara; Hübner, Harald; Gmeiner, Peter; Heinrich, Markus (Bioorganic & Medicinal Chemistry, 2015)
UnivIS-Import:2015-04-14:Pub.2015.nat.dchph.lphch.fluoro

Regiospecific Introduction of Halogens on the 2-Aminobiphenyl Subunit Leading to Highly Potent and Selective M3 Muscarinic Acetylcholine Receptor Antagonists and Weak Inverse Agonists - Fischer, Oliver; Hofmann, Josefa; Rampp, Hannelore; Kaindl, Jonas; Pratsch, Gerald; Bartuschat, Amelie; Taudte, Verena; Fromm, Martin; Hübner, Harald; Gmeiner, Peter; Heinrich, Markus (Journal of Medicinal Chemistry, 2020)
Muscarinic M-3 receptor antagonists and inverse agonists displaying high affinity and subtype selectivity over the antitarget M-2 are valuable pharmacological tools and may enable improved treatment of chronic obstructive pulmonary disease (COPD), asthma, or urinary incontinence. On the basis of known M-3 antagonists comprising a piperidine or quinuclidine unit attached to a biphenyl carbamate, S-fluoro substitution was responsible for M-3 subtype selectivity over M-2, while 3'-chloro substitution substantially increased affinity through a sigma-hole interaction. Resultantly, two piperidinyl- and two quinuclidinium-substituted biphenyl carbamates OFH243 (13n), OFH244 (13m), OFH3911 (14n), and OFH3912 (14m) were discovered, which display two-digit picomolar affinities with K-i values from 0.069 to 0.084 nM, as well as high selectivity over the M-2 subtype (46- to 68-fold). While weak inverse agonistic properties were determined for the biphenyl carbamates 13m and 13n, neutral antagonism was observed for 14m and 14n and tiotropium under identical assay conditions.
CRIS-Team WoS Importer:2020-05-15

Structure-guided development of selective M3 muscarinic acetylcholine receptor antagonists - Liu, Hongtao; Hofmann, Josefa; Fish, Inbar; Schaake, Benjamin; Eitel, Katrin; Bartuschat, Amelie; Kaindl, Jonas; Rampp, Hannelore; Banerjee, Ashutosh; Hübner, Harald; Clark, Mary J.; Vincent, Sandra G.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Keywords: Muscarinic receptor; Subtype selectivity; G protein-coupled receptor; Drug design; Crystal structure

Synthesis and evaluation of fluoro substituted pyridinylcarboxamides and their phenylazo analogues for potential dopamine D3 receptor PET imaging - Nebel, Natascha; Maschauer, Simone; Bartuschat, Amelie; Fehler, Stefanie; Hübner, Harald; Gmeiner, Peter; Kuwert, Torsten; Heinrich, Markus; Prante, Olaf; Hocke, Carsten (Bioorganic & Medicinal Chemistry Letters, 2014)
A series of fluoro substituted pyridinylcarboxamides and their phenylazo analogues with high affinity and selectivity for the dopamine D3 receptor was synthesized by the use of 6-fluoropyridine-3-carbonyl chloride (1) and fluorophenylazocarboxylic ester (2). Several of these compounds (9a-e and 10a-h) have been evaluated in vitro, among which 9b, 10a, 10c and 10d proved to have at least single-digit nanomolar affinity for D3. They also exhibit considerable selectivity over the other dopamine receptor subtypes and noteworthy selectivity over the structurally related serotonin receptor subtypes 5-HT1A and 5-HT2, offering potential radiotracers for positron emission tomography.
UnivIS-Import:2015-04-14:Pub.2014.nat.dchph.lphch.synthe_8
Keywords: Azoester; D3 receptor; Dopamine; Fluorine; Fluoroarylation; PET

Synthesis of Fmoc- and Boc-Protected (2S,5S)- and (2R,5R)-5-Aminomethylprolines - Bartuschat, Amelie; Hegmann, Nina; Heinrich, Markus (Synthesis-Stuttgart, 2019)
The proline derivatives (2S, 5S) dmamPro, (2S, 5S) N-Boc-amPro and (2R, 5R) dmamPro are useful building blocks for peptides since they allow conformational fixation of peptidyl-CO-N-prolyl bonds in the unusual cis conformation. The stereoselective syntheses of these dimethylaminomethyl- prolines is achieved from literature-known precursors with overall yields of 23% [over 8 steps for (2S, 5S) dmamPro], 33% [over 9 steps for (2S, 5S) N-Boc-amPro] and 12% [over 8 steps for (2R, 5R) dmamPro]. The applicability of (2S, 5S) N-Boc-amPro in peptide synthesis is demonstrated through the preparation of an Fmoc-Val-amPro- OMe dipeptide.
CRIS-Team WoS Importer:2019-03-06